2014
DOI: 10.3168/jds.2014-8319
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the systemic innate immune response and metabolic alterations of nonlactating cows with diet-induced subacute ruminal acidosis

Abstract: Subacute ruminal acidosis (SARA) increases lipopolysaccharide endotoxin in the rumen, which might translocate into the systemic circulation, triggering a cascade of clinical and immunological alterations. The objective of this study was to characterize the clinical immune and metabolic responses to ruminal-derived lipopolysaccharide in nonlactating cows induced with SARA using 2 challenges, a grain-based SARA challenge (GBSC) or an alfalfa-pellet SARA challenge (APSC). Six dry, nonlactating Holstein cows were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 34 publications
4
24
1
Order By: Relevance
“…Animals 2020, 10, x FOR PEER REVIEW 9 of 14 and the downregulation of HMGCR expression in the liver suggest that cholesterol synthesis was being regulated during an acute response to ruminal acidosis and that the regulation of cholesterol synthesis began in the liver. Previous experiments have demonstrated that plasma glucose concentrations increase by as much as 6% during ruminal acidosis caused by increased concentrate feeding [36]. In the current study, glucose concentrations were 39% and 41% greater (p < 0.01) in wethers sampled from P2 and P3, respectively, when compared to the wethers sampled during the P1 (Table 5).…”
Section: Resultssupporting
confidence: 51%
“…Animals 2020, 10, x FOR PEER REVIEW 9 of 14 and the downregulation of HMGCR expression in the liver suggest that cholesterol synthesis was being regulated during an acute response to ruminal acidosis and that the regulation of cholesterol synthesis began in the liver. Previous experiments have demonstrated that plasma glucose concentrations increase by as much as 6% during ruminal acidosis caused by increased concentrate feeding [36]. In the current study, glucose concentrations were 39% and 41% greater (p < 0.01) in wethers sampled from P2 and P3, respectively, when compared to the wethers sampled during the P1 (Table 5).…”
Section: Resultssupporting
confidence: 51%
“…Therefore, it is the closest and most accurate indicator of rumen health or disorders such as SARA, because it provides direct information about the conditions within the rumen (Enemark ). Rumen pH <6 for a prolonged period for several hours a day can adversely leads to acidosis, (Rodríguez‐Lecompte et al ). Recently, Zhao et al () indicated that SARA produces a high concentration of ruminal LPS, which over activates the inflammatory pathways and significantly increases the expression and synthesis of pro‐inflammatory cytokines in the rumen epithelium, thus causing partial inflammation of the rumen.…”
Section: Impact Of Feeding Single‐cell Fungi On Rumen Fermentation Acmentioning
confidence: 99%
“…Recently, Zhao et al () indicated that SARA produces a high concentration of ruminal lipopolysaccharides (LPS), which over‐activates the inflammatory pathways and significantly increases the expression and synthesis of proinflammatory cytokines in the rumen epithelium, thus causing partial inflammation of the rumen. Low rumen pH ranging from 5–6 for prolonged periods can negatively affect feed intake, microbial metabolism, and nutrient degradation, erratic appetite, body weight loss, ruminal motility, stasis, hyperkeratosis, and leads to acidosis, inflammation, laminitis, diarrhoea and villi wear out and bloat (Rodríguez‐Lecompte et al ). One of the consequences of a low rumen pH is the reduction/elimination of protozoa, the most effective mycotoxin degraders among the rumen microbial community.…”
Section: Introductionmentioning
confidence: 99%
“…Another cause could also be local inflammation or damage to the ruminal epithelium, as commonly reported as a pathological finding in SARA (Kleen et al., ). The activation of an APR during SARA does not usually affect other clinically detectable inflammatory signs, such as increased rectal temperature, plasma fibrinogen, white blood cell count and differentials (Gozho et al., ; Li et al., Rodríguez‐Lecompte et al., ) and also total plasma proteins, globulins, fibrinogen and albumin concentrations typically remain within reference values of healthy cows (Rodríguez‐Lecompte et al., ). Acute‐phase proteins could provide realisable biomarkers of SARA.…”
Section: Blood Variablesmentioning
confidence: 99%